Risk management of short supply chain of Momotaro Tomato Commodity in PT. Saribhakti Bumi Agri - Azizah Rahmi Raharja; Agriani Hermita Sadeli; Nur Syamsiyah; Sulistyodewi Nur Wiyono (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
Momotaro tomato is an introduced vegetable commodity in West Java. Development of introduced vegetables needs an effective and effi cient supply chain performance to maintain the quality and quantity of the product until it reaches the consumers. PT. Saribhakti Bumi Agri is an agribusiness company that cultivates and sells introduced vegetables with shorter supply chain fl ows. Short supply chain has various benefi ts including lower prices and direct quality control by consumers.